The Development of Health Literacy Promoting Model of Colorectal Cancer Patients Receiving Chemotherapy - Poosuwan, Roongporn; Jansook, Naruemon; Dunkum, Saranya (Journal of Preventive Medicine Association of Thailand, 2020)
The objectives of this research and development were to 1) study health literacy of colorectal cancer patients receiving chemotherapy 2) study situation of promoting health literacy in colorectal cancer patients receiving chemotherapy 3) develop the pattern of health literacy promoting model of colorectal cancer patients receiving chemotherapy, and 4) study the effectiveness of health literacy promoting model of colorectal cancer patients receiving chemotherapy in Jainadnarendra Hospital. The research was divided into 4 steps including: 1) survey of health literacy of colorectal cancer patients receiving chemotherapy. Sample was 70 colorectal cancer patients receiving chemotherapy. The research instrument used was a questionnaire. The data was analyzed by descriptive statistics; 2) study of situation promoting health literacy in colorectal cancer patients receiving chemotherapy. Focus group discussion was conducted among 9 informants. Data were analyzed using content analysis; 3) developing the health literacy promoting model of colorectal cancer patients receiving chemotherapy. The researcher used the findings from the first, and the second step to develop the health literacy promoting model namely SMILE model; 4) study the effectiveness of the SMILE model. Sample was 60 colorectal cancer patients receiving chemotherapy. The research instruments were the SMILE model, and the questionnaire regarding health literacy. Data were analyzed using Paired t-test. The results revealed as follows; 1. Overall, colorectal cancer patients receiving chemotherapy had health literacy at low level. (M=48.51, S.D.=7.32) 2. Situations of promoting health literacy in colorectal cancer patients receiving chemotherapy included lack of 1) integrating health literacy promoting with work 2) model or activity, and 3) monitoring and evaluation of health literacy that is clear and continuous. 3. The SMILE model included 1) S: Survey, 2) M: Meeting, 3) I: Implementation 4) L: Learning, and 5) E: Evaluation 4. After using the SMILE model, the experimental group had health literacy higher than before using the model and higher than control group with statistical significance (p<.01)